2015
DOI: 10.17245/jdapm.2015.15.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Using nasal cannula for sevoflurane deep sedation in emergency dental treatment

Abstract: BackgroundEmergency room doctors run into difficulties in treating injured pediatric patients because usually they fell into panic after trauma. In these situation, deep sedation with sevoflurane is fully recommendable method. The conventional way can interrupt common dental treatment procedure.MethodsIn the present study, nasal cannula was used for sevoflurane deep sedation in 11 dental emergency treatment. Age ranged from 0 to 3 years old (average of 1.8 years).ResultsTreatment duration was from 10 to 35 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
3
0
3
Order By: Relevance
“…The results of this study regarding recovery time indicated a success of sevoflurane versus propofol traditionally used for deep sedation. This result is consistent with previous studies that reported speed recovery time when sevoflurane is used to sedated pediatric dental patients (Lee et al, 2004;Kim et al, 2013;Kim et al, 2015). Through this study, no statistically significant differences were found between the propofol and sevoflurane groups with regard to efficacy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study regarding recovery time indicated a success of sevoflurane versus propofol traditionally used for deep sedation. This result is consistent with previous studies that reported speed recovery time when sevoflurane is used to sedated pediatric dental patients (Lee et al, 2004;Kim et al, 2013;Kim et al, 2015). Through this study, no statistically significant differences were found between the propofol and sevoflurane groups with regard to efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…children. Many studies have stated that intravenous and inhalation deep sedation is the safest and most effective sedation(Ozer et al, 2011;Badina et al, 2006;Kim et al, 2015). Sedation in children differs from sedation in adults.…”
mentioning
confidence: 99%
“…It may be necessary to initiate sedation with a Mapleson circuit to quickly reach these concentrations, as this can be more difficult due to nasal prong leaks through the nose and mouth [ Table 1 ]. [ 39 40 41 ]…”
Section: Sedationmentioning
confidence: 99%
“…However, the use of sevoflurane is absolutely contraindicated in children with a history of or susceptibility to malignant hyperthermia. [ 39 40 41 ]…”
Section: Sedationmentioning
confidence: 99%
“…Produce hipnosis, amnesia, analgesia e inmovilidad. Se ha descrito su uso a través de cánula nasal o máscara facial para la sedación moderada a profunda, con mantenimiento de ventilación espontánea, tanto para procedimientos quirúrgicos con anestesia neuroaxial o regional, como para procedimientos fuera del quirófano, tales como estudios de resonancia magnética, endoscopia de vía digestiva, inserción de catéteres venosos centrales, procedimientos odontológicos, sedación en unidad de cuidados intensivos, entre otros; con estudios que lo comparan con anestésicos intravenosos y reportan tiempos de inicio de sedación comparables, mejores condiciones durante el mantenimiento de la sedación, tasas de complicaciones pulmonares y hemodinámicas más bajas y un tiempo de recuperación más rápido [16]- [24]. • Dosis: se ha descrito su administración por medio de máscara facial, con un flujo de oxígeno a 4 L/min y el dial del vaporizador de sevoflurano de 4%-6%.…”
unclassified